Numerical Evaluation of the Forced Vibration Response of a Timoshenko Beam Subjected to a Moving Force Using the Modal Analysis Approach - Nguyen, Thi Van Huong; Nguyen, Sy Nam; Nguyen, Van Khang (JST: Engineering And Technology For Sustainable Development, 2022)
The dynamic response of a structure subjected to moving loads is an interesting and meaningful research subject in various engineering fields such as bridges, roadways, railways and aircrafts. The present paper deals with the dynamic response of an uniform Timoshenko beam under the action of a moving force. Properties of the natural frequencies and modes of the Timoshenko beam are discussed. It is shown that the solution of the forced vibration for the transverse displacement and the rotation of the cross section of the beam can be expressed in form of a sum of two infinite series. The numerical simulation result shows that the speed change of the moving force has little effect on the beam deflection, but its magnitude change greatly affects the beam deflection.